Processos redoxes de ferro em argilominerais: caracterização, métodos de quantificação, especiação e modificações estruturais - Alexandre dos Santos Anastacio (2007)
Redox processes within clays and clay minerals influence significantly in different physical and chemical properties in soils and sediments, mainly which ones related to the chemical interaction between solid and solution phases (liquid or gas) such as superficial charge and ion dynamics. Other, like expansibility, water retention capacity, surface area, and magnetic properties can also be conditioned to iron redox.The present work were dedicated to the study of forms and distribution of iron in clays and clay minerals prepared in controlled conditions in the laboratory in order to access information about how theses processes influence the suitability of such materials in environmental remediation. Chemical reduction was compared including biological reduction. Elementary composition and oxidation state of iron were monitored by wet chemical analyses, and Mössbauer spectroscopy, complementary techniques were also used such as X-ray diffractometry, thermal analysis, and Fourier-transform infrared spectroscopy. Materials were characterized in three different treatment conditions: (i) inaltered state of sampling or as received by commercial sources, (ii) chemically orbiologically reduced by biostimulation and reoxidized or (iii) chemically modified by pillaring. The main objectives of these studies were: (i) characterize structural modifications due to chemical reduction in clays and clay minerals (Brazilian clay fractions and a standard clay SWa-1), as function of reaction time and reductant amount; (ii) characterize a clay from the Kutch region India in order to evaluate the potential use as filling material in high level radioactive waste barriers; (iii) compare wet iron analysis speciation methods more common in the literature: the ferrozine(with modifications in the conventional protocol) and phenantroline methods, and (iv) characterize and test the catalytic efficiency of pillared clays with different Fe/(Fe + Al). As result of chemical reduction ferruginous minerals of the studied materials suffered structural modifications: (i) from Brazilian clay fractions (Cambisoland Vertisol) due to almost complete dissolution of the iron oxide phases and reduction of structural iron in the silicates (as a novel finding the magnetic ordering in the SWa-1 sample with more than 4 wt % ferrous iron content at 4 K), and (ii) due to reduction and subsequent iron oxide phases dissolution from the Kutch clay sample (in the unaltered state the clay is comprised of smectite, kolinite, and maghemite, and superparamagnetic goethite and hematite), where goethite and hematite were dissolved but maghemite resisted to the treatment; by reoxidation, where no magnetically ordered sextet were restored, indicating that iron was present only in the silicates structure and/or in small clusters such that no magnetic interaction could be produced, and (iii)by iron speciation, as revealed by chemical analysis, where the conventional ferrozine method (0.5 mol L-1 extraction) indicated erratic Fe(II) valuesand overestimation of total iron content in silicates (probable error sources are the incomplete dissolution in the HCl extractant and photo-sensibility of the ferrozine complex). Characterization of pillared clays indicated that the iron pillars precursor was akaganeite which converted to hematite if treated in the same pillaring conditions(300 °C for 3 h). Such transformation did not occur in the presence of the suspension clay in the pillaring process. In the Fe/(Al +Fe) ratio series, the hyperfine fields did not change significantly with increasing of the aluminum content indicating that no incorporation of aluminum in the hydroxide structure and mixed Al-Fe pillars were formed. Upon reduction only a small portion (4 %) from the pillars was resistant to thetreatment and bonded to the clay surface or in small clusters. Moreover, the chemical reduction increased the catalytic activity due to increase of porosity and the presence of Fe(II) in the structure. Catalytic activity increased with aluminum content in the pillars. Methods of chemical reduction can modify crystal structures and magnetic properties of clays minerals; alter physical-chemical processes which are fundamentalto catalytic activity in decomposition of organic molecules. Thus, iron reduction can be used in the preparation of novel materials technologically attractive for environmental remediation.